Urgensi Kelekatan Dalam Perkembangan Jiwa Anak - Moh. Ali Murtadlo (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2021)
The attachment in the children’s psychological development is very important. The children who have been given a good attacment from their parent will get  a positive  psichological development, such as feeling safe, being able to explore, woking model of their reviving relationship, being conficeent, developing his intelactual potential, being capable of thingking logically, being capable of developing  his emphaty, being capable of coping with stress and frustration, being  capable of coping with fear and enxiety as well as being capable of developing a good social relationship with people. Clearly, it gives children an opportunity to explore the environment comfortably.